REVOLUTIONIZING VASCULAR SURGERY: A COMPREHENSIVE REVIEW OF NOVEL DEVICES AND TECHNOLOGIES SHAPING THE FUTURE OF PATIENT CARE - Barreto, Ana Julia Nassar; Lima, Bruna Marmori; Pádua, Ana Carolina Diniz e; Destefani, Afrânio Côgo; Destefani, Vinícius Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
Vascular surgery has undergone significant advancements in recent years, with the introduction of innovative devices and technologies that have transformed patient care and surgical outcomes. This review aims to provide a comprehensive overview of the latest developments in vascular surgery, focusing on novel devices that have emerged to address longstanding challenges in the field. The review explores six key areas: vessel sealing devices, vascular ultrasound technologies, hemodialysis vascular access devices, robotic-assisted endovascular surgery systems, sutureless vascular anastomotic devices, and bioartificial vascular implants. The synthesis of the current evidence and expert opinions offers valuable insights into the transformative impact of these technologies on vascular surgery and patient care, as well as the associated challenges and considerations for their optimal implementation in clinical practice.